An Analysis upon the Contribution of Media Communication in National Development: Continuity and Challenges: Exploring the Role of Media Communication in Rural Development and Cultural Preservation (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Development has turned into the worldwide 'common religion', since the previous 40 years-and a rallying call for all nations - rich or poor, solid or feeble. It is a long and complex developmental process-more a process of social change as opposed to only age and aggregation of material assets. Researchers have proposed different hypotheses and models while development offices set different objectives for the development of nations and a portion of the speculations have neglected to yield comes about and new hypotheses that rose have attempted to offer answers for accelerate development. The positive part of development has been perceived in underdeveloped nations since information dissemination assumes a key part in bringing a social change among the collectors. Analysts have agreed need to dispersion of information to the recipient through relational and mass communication channels. In the present dynamic world, communication and its part has turned out to be extremely particular and huge. In India, present day mass media alone can't reach to the a large number of individuals in rural areas who have no normal access to TV, newspapers, internet and so on because of poverty and illiteracy. The cutting edge media's compass is to a great extent limited to urban areas. Information, education and excitement don't reach to a huge dominant part of the general population in rural and remote areas. The mass media has ended up being charming, indifferent and fantastic. Therefore, the cutting edge media isn't reasonable for saving cultural legacy and advancement of people performing customs and expressions. The people media has momentous effect on rural society in view of the worthy maxims, practical centrality and the cultural esteems. Society media can beat the challenges of language, discourse, words and different hindrances of communication like enthusiasm, understanding, translation, mentality and observation. Society media is a standout amongst the most essential vehicles of social change and nation building.